Simple realization of quadrature sinusoidal oscillator with independent control - Chaichana, Amornchai; Jaikla, Winai (My University, 2017)
In this paper, a new sinusoidal oscillator is proposed. As a interesting feature, the proposed oscillator provides two sinusoidal voltage waveforms with 90° degree phase difference without the requirement of additional phase shifter circuit. The proposed circuit employs only a voltage differencing current conveyor (VDCC), three resistors and two grounded capacitors. The frequency of oscillation (FO) and condition of oscillation (CO) can be independently controlled. Also, the tuning of frequency of oscillation can be done electronically. The use of single active is highly attractive from integration point of view. PSPICE simulations using 0.18μm CMOS parameters and supply voltage of ±0.9V demonstrates a precise operation.
Keywords: CMOS; Oscillator; Sinusoidal waveform; VDCC